STATES AND TRANSNATIONAL CORPORATIONS: PERSPECTIVES OF DEVELOPMENT IN GLOBALIZATION CONDITIONS - Слатенькова, М. О. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
With every step expansion of globalization, which is partly due to including a number of integration processes and the growing importance of scientific and technological progress, we observe a very complex situation associated with changing opportunities and the importance of the state. This is due above all to the active influence of the policies and activities of transnational corporations on the national economic system. The article reveals the question of finding a consensus between the state and multinational corporations for creating conditions that will contribute to further economic growth.